Neuragrion mysticum (Odonata: Megapodagrionidae) demystified - Von Ellenrieder, Natalia (2005)
Based on circumstantial evidence, Neuragrion mysticum Karsch, 1891 is considered a junior synonym of Heteropodagrion sanguinipes Selys, 1885. Annotated wing scans for H. sanguinipes and Mesagrionleucorrhinum Selys, 1885, species originally compared to N. mysticum, are provided.